Analysis of the Upgrading Effect of the Industrial Structure of Environmental Regulation: Evidence From 113 Cities in China - Shao, Wei; Yin, Yufei; Bai, Xiao; Taghizadeh-Hesary, Farhad (Frontiers in Environmental Science, 2021)
At present, China's economy is in a crucial period of economic structural transformation. To alleviate the downward pressure on the economy and explore sustainable growth paths, the Chinese government has issued several environmental regulations. However, the impact of environmental regulation on industrial structure upgrading has not been carefully examined yet. This paper utilizes the Pollution Information Transparency Index (PITI) to measure environmental regulation (ER) and examines the impact of ER on industrial structure upgrading (ISU). The sample cities are divided into 36 resource-based cities (RBCs) and 77 non-resource-based cities (NRBCs). The panel data containing 113 cities during 2008-2017 are used in this paper. The empirical results show that ER has a significant impact on ISU of RBCs and NRBCs and robust tests proved the reliability of this result. Analysis of heterogeneity shows ER has a more substantial role in promoting ISU in RBCs and the eastern region. Meanwhile, inside RBCs, ER has a more substantial impact on ISU in growth-RBCs than other RBCs. The mechanism test shows that the mediation effect of technological innovation in RBCs and NRBCs is significant. At last, the impact of ER on ISU has a double-threshold effect in RBCs and a single threshold effect in NRBCs. With the technological innovation progress, ER produces an increasing effect on ISU of RBCs and NRBCs.